The use of standardization in IT systems in health care - Czubek, Andrzej; Szymańska, Jolanta; Byczyński, Edward; Skrzypek, Mariusz (Polish Journal of Public Health, 2012)
Standardization is one of the important tools for the implementation of EU policies to ensure the competitiveness of enterprises and the elimination of barriers to trade within the EU. The European Commission “e-Health Action Plan” (2004) recognized the interoperability of information systems in health care as one of its priorities. Standardization, in turn, is a prerequisite to ensure interoperability.The authors examined the extent to which standardization is reflectead in the key acts on the informatization of health care:• The Directives for Informatization “eHealth Poland” for 2011-2015, approved by the management of the Ministry of Health,• Act of 28 April 2011 on the information system in health care (Journal of Laws of 2011, No. 113, item. 657, as amended).Lack of effective comprehensive legal solutions in the field of standardization, especially at the statutory level has been confirmed. This complicates the process of informatization in terms of interoperability. According to the authors this lack meant that in most of the implemented systems generally no valid standardization solutions were implemented and thus the interoperability. The standardization initiative under the responsibility of the Polish Committee for Standardization was not used either.